2019
DOI: 10.1108/jsm-04-2018-0124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consumer emotions on outcome behaviors following service failure

Abstract: Purpose The purpose of this paper is to explore the role of emotions that consumers experience following service failures and to assess the effects of each of these emotions on important behavioral outcomes. Design/methodology/approach This paper extends the work of Wetzer et al. (2007) and draws upon the existing literature to test a series of research hypotheses tying emotions to four important behavioral outcomes primarily using stepwise regression. Findings When a service failure occurs, customers expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 85 publications
(197 reference statements)
5
75
0
3
Order By: Relevance
“…Emotions (Grandey et al, 2004; Ruth et al, 2002), and in particular frustration are a key element in customer satisfaction and loyalty in service encounters (Gelbrich, 2010; Guchait & Namasivayam, 2012; Van Steenburg et al, 2013). Failure is known to generate a variety of negative emotions, such as anger, regret or frustration (Antonetti et al, 2020; Gelbrich, 2010; Harrison‐Walker, 2012, 2019a; Hudson et al, 2017). Using a valence‐based approach to emotions, Smith and Bolton (2002) showed that the magnitude and type of service failure impacted negative emotions with subsequent effects on satisfaction.…”
Section: Emotions After Service Failurementioning
confidence: 99%
“…Emotions (Grandey et al, 2004; Ruth et al, 2002), and in particular frustration are a key element in customer satisfaction and loyalty in service encounters (Gelbrich, 2010; Guchait & Namasivayam, 2012; Van Steenburg et al, 2013). Failure is known to generate a variety of negative emotions, such as anger, regret or frustration (Antonetti et al, 2020; Gelbrich, 2010; Harrison‐Walker, 2012, 2019a; Hudson et al, 2017). Using a valence‐based approach to emotions, Smith and Bolton (2002) showed that the magnitude and type of service failure impacted negative emotions with subsequent effects on satisfaction.…”
Section: Emotions After Service Failurementioning
confidence: 99%
“…The lack of responsiveness towards meeting consumers' needs or empathy regarding the consequences of disappointing the consumers represents multiple service failures. The cumulative effects of such service failures are likely to provoke negative affective responses leading to poor service evaluation and ultimately value-destruction (Harrison-Walker, 2019).…”
Section: Experiencesmentioning
confidence: 99%
“…Experiences for these kinds of consumers may also be influenced by the opinions of third parties such as caregivers and companions [28]. The result of the experience may be satisfactory or unsatisfactory and will affect the customer's behavior, generating memories that will determine their loyalty or degree of recommendation [29]. Another result of the experience is the customer's involvement in future co-creation of experience.…”
Section: Conceptual Background 21 the Visitor With Disabilities Experiencementioning
confidence: 99%
“…However, they can try to know their visitors, and design and manage interaction points to influence perceptions, thus increasing interest, involvement, satisfaction, loyalty, and support [35]. Indeed [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] all point out the importance of identifying environments that produce different touchpoints and generate customer experience.…”
Section: Inclusive Management Of the Visitor With Disabilities Experience: Relational Spacesmentioning
confidence: 99%